Cardiac adaptation to high altitude in the plateau pika (Ochotona curzoniae). Issue 2 (18th July 2013) - Pichon, Aurélien; Zhenzhong, Bai; Marchant, Dominique; Jin, Guoen; Voituron, Nicolas; Haixia, Yun; Favret, Fabrice; Richalet, Jean‐Paul; Ge, Ri‐Li
Abstract The aim of this study was to assess maximal heart rate (HR) and heart morphological changes in high altitude living "plateau pikas" and rats bred at 2260 m. Rats and pikas were catheterized to measure HR (2260 m). After baseline measurements, 1 mg/kg of atropine (AT) and increasing doses of isoproterenol (IsoP) (0.1, 1, 10, and 100 μg kg) were injected into animals. Right (RV) and left ventricles (LV) were removed to calculate Fulton's ratio (LV + septum (S) to RV weights) and to assess mRNA expression level of β1‐ and β2‐adrenoceptors, muscarinic m1 and m2 receptors, and vascular endothelial growth factor (VEGF). Resting HR was significantly lower in rats than in pikas and increased after AT injection only in rats. IsoP injection induced a significant increase in HR in rat for all doses, which was systematically greater than in pikas. In pikas HR was slightly increased only after the two highest concentrations of IsoP. Fulton's ratio was greater in rats compared with pikas but the LV + S adjusted for body weight was greater in pikas. Pikas showed lower β1‐adrenoceptors and muscarinic m2 receptors mRNA expression but larger VEGF mRNA expression than rats both in RV and LV. These results suggest that pikas have a lower maximal HR compared with rats certainly due to a decrease in β‐adrenergic and muscarinic receptors mRNA expression. However, the LV hypertrophy probably led to an increase in stroke volume to maintain cardiac output in response to the cold and hypoxic environment.